ОСОБЛИВОСТІ ТА ВИДИ ЮРИДИЧНОЇ ВІДПОВІДАЛЬНОСТІ ДЕРЖАВНОЇ МИТНОЇ СЛУЖБИ ЯК СУБ’ЄКТА ЗАПОБІГАННЯ ТА ПРОТИДІЇ ЗЛОЧИННОСТІ - Черкасський, Руслан Анатолійович (SUPREMANCE OF LAW, 2016)
The article, based on the analysis of scientific views of scientists and current legislation of Ukraine, describes three key types of legal liability of the State Customs Service as a subject of combating and preventing crime. Gaps and shortcomings of the current legislation governing the research are pointed out.